LMR‐101, a novel derivative of propofol, exhibits potent anticonvulsant effects and possibly interacts with a novel target on γ‐aminobutyric acid type A receptors. (8th January 2021) - Zhao, Yi; An, Long; Guo, Shupan; Huang, Xiaoxing; Tian, Huajie; Liu, Li; Chen, Tao; Sun, Xun; Mei, Qibing; Wang, Rutao
Abstract: Objective: LMR‐101 is a bisphenol derivative of propofol, a short‐acting general anesthetic, which is also used to manage status epilepticus (SE). We evaluated the sedative and anticonvulsant effects of LMR‐101 to discover its potential to manage epilepsy and SE in the clinic. Methods: Comparative studies between LMR‐101 and propofol were performed in mice to elucidate an appropriate dose range for LMR‐101 that produced anticonvulsant effects without significant sedation. Then, the anticonvulsive efficacy for LMR‐101 was evaluated using seizure models induced by pentylenetetrazol and (+)‐bicuculline. The ability of LMR‐101 to inhibit SE was assessed using a rat model of SE induced by pilocarpine. Radioligand binding assay profiles for LMR‐101 were performed to evaluate the potential mechanisms of action underlying its anticonvulsant properties. Results: In the mouse study, LMR‐101 exhibited greater anticonvulsant and lesser sedative effect compared with propofol. LMR‐101 completely inhibited pentylenetetrazol‐induced seizures at a dose of 50 mg/kg and exhibited heavy sedation at 300 mg/kg. Propofol anesthetized all mice and only decreased the seizure rate at 25 mg/kg. LMR‐101 also suppressed seizure behaviors evoked by (+)‐bicuculline in mice in a dose‐dependent manner. In the pilocarpine‐induced SE model, LMR‐101 significantly decreased the maximum seizure score and seizure duration in a dose‐dependent manner. The median effective dose for LMR‐101 was 14.30 mg/kg and 121.87 mg/kg to prevent and inhibit sustained SE, respectively. In binding assays, LMR‐101 primarily inhibited tert ‐[ 35 S] butylbicyclophosphorothionate binding to γ‐aminobutyric acid type A (GABAA ) receptors (half‐maximal inhibitory concentration = 2.06 μmol·L –1 ), but it did not affect [ 3 H] flunitrazepam or [ 3 H] muscimol binding. Significance: It is anticipated that LMR‐101 might play an essential role in the clinical management of epilepsy and SE. LMR‐101 also might bind to a novel target site on the GABAA receptor that is different from existing antiepileptic drugs. Further study of the mechanisms of action of LMR‐101 would be of considerable value in the search for new active drug sites on GABAA receptors.